Multimodal Strategi untuk Meningkatkan Kepatuhan Hand Hygiene - Wartini, Wartini; Komariah, Maria; Nurhakim, Furkon (Journal of Telenursing (JOTING), 2024)
This research aims to identify multimodal strategies to increase hand hygiene compliance. The method used was a literature study using PubMed, Scient Direct, and Ebsco, with inclusion criteria for articles focusing on multimodal hand hygiene strategies, publications in 2013-2023, available in full text in English. The research results from thirteen analyzed articles showed increased hand hygiene compliance among health workers. Seven articles showed the highest compliance among nurses. Significant improvements show varying results depending on the type of health worker, care unit, and type of intervention. The multimodal hand hygiene strategy comprises five components: system change, education and training, observation and feedback, workplace reminders, and institutional safety climate—conclusion: Multimodal intervention strategies can increase hand hygiene compliance among health workers. Keywords: Compliance, Nurses, Multimodal Hand Hygiene Strategy This research aims to identify multimodal strategies to increase hand hygiene compliance. The method used was a literature study using PubMed, Scient Direct, and Ebsco, with inclusion criteria for articles focusing on multimodal hand hygiene strategies, publications in 2013-2023, available in full text in English. The research results from thirteen analyzed articles showed increased hand hygiene compliance among health workers. Seven articles showed the highest compliance among nurses. Significant improvements show varying results depending on the type of health worker, care unit, and type of intervention. The multimodal hand hygiene strategy comprises five components: system change, education and training, observation and feedback, workplace reminders, and institutional safety climate—conclusion: Multimodal intervention strategies can increase hand hygiene compliance among health workers. Keywords: Compliance, Nurses, Multimodal Hand Hygiene Strategy